LC3‐association with the parasitophorous vacuole membrane of Plasmodium berghei liver stages follows a noncanonical autophagy pathway. (19th June 2017) - Wacker, Rahel; Eickel, Nina; Schmuckli‐Maurer, Jacqueline; Annoura, Takeshi; Niklaus, Livia; Khan, Shahid M.; Guan, Jun‐Lin; Heussler, Volker T.
Summary: Eukaryotic cells can employ autophagy to defend themselves against invading pathogens. Upon infection by Plasmodium berghei sporozoites, the host hepatocyte targets the invader by labelling the parasitophorous vacuole membrane (PVM) with the autophagy marker protein LC3. Until now, it has not been clear whether LC3 recruitment to the PVM is mediated by fusion of autophagosomes or by direct incorporation. To distinguish between these possibilities, we knocked out genes that are essential for autophagosome formation and for direct LC3 incorporation into membranes. The CRISPR/Cas9 system was employed to generate host cell lines deficient for either FIP200, a member of the initiation complex for autophagosome formation, or ATG5, responsible for LC3 lipidation and incorporation of LC3 into membranes. Infection of these knockout cell lines with P .  berghei sporozoites revealed that LC3 recruitment to the PVM indeed depends on functional ATG5 and the elongation machinery, but not on FIP200 and the initiation complex, suggesting a direct incorporation of LC3 into the PVM. Importantly, in P .  berghei ‐infected ATG5 −/− host cells, lysosomes still accumulated at the PVM, indicating that the recruitment of lysosomes follows an LC3‐independent pathway.